Various health-related challenges amidst recent floods in Pakistan; strategies for future prevention and control. (October 2022) - Ochani, Sidhant; Aaqil, Syeda Ilsa; Nazir, Abubakar; Athar, Fatima Binte; Ochani, Khushi; Ullah, Kaleem
Abstract: Floods catastrophes are the most frequent hazards globally. According to the Center for Research on the Epidemiology of Disasters (CRED), a total of 432 catastrophic events were recorded in 2021, among which flood dominated with 223 occurrences alone. Flood catastrophes have significantly increased morbidity and mortality universally. It has made life more vulnerable in the context of numerous risks and calamities. During the flood, epidemics and outbreaks are most common affecting a larger population. People face various problems amidst floods like infectious diseases, reproductive health, and even mental health issues. Pakistan is currently one of the most frequently flood-affected nations in the world. As Pakistan continues to be devastated by monsoon flooding and torrential rains, 1290 people have died, 1, 468, 019 homes have been partially or completely destroyed, and 736, 459 animals have perished. To plan an efficient health care program, it is crucial to know the common problems that frequently affect people during floods.